Religion and the disjunction of the facts and values in economics - Maldeikienė, Aušra (Religija ir kultūra, 2008)
The article an attempt to divulge the origins of the methodological and, in part, theoretical principles of the economics. In highlighting the methodological assumptions of the issue, economic studies expose the notion of distinction between utility and meaning: by disproportionately emphasizing the utility dimension, the plane of meaning is hidden or even eliminated, inevitably incorporating the religious component as well. Methodological origins of the utility/meaning distinction are encountered in the prevailing concept of economic basis and means, where particular consideration is given to the comprehension of a rational, economic individual, as well as to the distinction between positive and normative economies. This demonstrates how the internal contradiction of a rational individual’s comprehension and the distinction of positive/normative economy give rise to fact-value distinction that is particularly deeply rooted in the very foundation of mainstream economic theory. The study shows how the utility/meaning and, accordingly, the fact/value distinctions which have occupied the methodological field of economy are manifested as expressions of the active/passive, technical and meditative existence concealed within an individual’s economic being. Within this context there is also an endeavor to substantiate the specific circumstance of so-called Christian economics, when Christian philosophical and theological insights are used in an attempt to furnish solutions to particularly concrete economic problems.